Evaluating indicators of energy security for sustainable development in Asia - Zhou, Yixiao; Cabalu, H. (Taylor & Francis Ltd, 2018)
Helen Cabalu and Yixiao Zhou, in “Evaluating indicators of energy security for sustainable development in Asia,” examine the fossil fuel energy profile of selected Asian countries in terms of specific energy supply indicators, which include intensity, net import dependency, ratio of domestic energy production to total domestic energy consumption and geopolitical risk. Drs. Cabalu and Zhou discuss the indicators for selected countries in Asia in the period between 2002 and 2015. A composite supply security index for oil (OSSI), gas (GSSI) and coal (CSSI) are calculated to provide a quantitative measure of energy security for each of the fossil fuels, taking into account the dynamics among the identified set of energy supply indicators. The authors examine the energy profile of selected Asian countries, including China, India, Japan, Korea, Singapore and Thailand, then compile a supply security index for oil, gas and coal, analyzing and evaluating the index in order to draw policy conclusions.